(untitled) (Clinics, 2021)
OBJECTIVES: Contrast-induced acute kidney injury (CI-AKI) is an important clinical problem that can be aggravated by diabetes mellitus, a major risk factor. However, heme oxygenase-1 (HO-1), a promising therapeutic target, can exert antioxidant effects against CI-AKI. Thus, we investigated the role of HO-1 in CI-AKI in the presence of diabetes mellitus. METHODS: Twenty-eight male Wistar rats weighing 250-300g were subjected to left uninephrectomy, and concomitantly, diabetes induced by streptozotocin (65 mg/kg). After 12 weeks, iodinated contrast (meglumine ioxithalamate, 6 mL/kg) and hemin (HO-1 inducer-10 mg/k) were administered 60 min before iodinated contrast treatment. The rats were randomly divided into four groups: control, diabetes mellitus (DM), DM iodinated contrast (DMIC), and DMIC hemin (DMICH). Kidney function, albuminuria, oxidative profile, and histology were assessed. All experimental data were subjected to statistical analyses. RESULTS: CI-AKI in preclinical diabetic models decreased creatinine clearance and increased urinary neutrophil gelatinase-associated lipocalin (NGAL) levels and the degree of albuminuria. Additionally, the levels of oxidative and nitrosative stress metabolites (urinary peroxides, thiobarbituric acid-reactive substances, and NO) were elevated, while thiol levels in kidney tissue were reduced. Kidney histology showed tubular cell vacuolization and edema. HO-1 inducer treatment improved kidney function and reduced urinary the NGAL levels. The oxidative profile showed an increase in the endogenous thiol-based antioxidant levels. Additionally, the tubular injury score was reduced following HO-1 treatment. CONCLUSIONS: Our findings highlight the renoprotective effects of HO-1 in CI-AKI and preclinical diabetic models. Therefore, HO-1 ameliorates kidney dysfunction, reduces oxidative stress, and prevents cell necrosis.